2004
DOI: 10.1007/s10147-004-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy as a bladder-preservation approach for muscle-invasive bladder cancer: current status and perspectives

Abstract: Radical cystectomy has been considered the gold standard for the treatment of muscle-invasive bladder cancer. However, because of disappointing results with radical surgery in terms of survival and decreased quality of life (QOL), bladder-preservation treatment has been introduced as an alternative to radical cystectomy. The primary purpose of the bladder-preservation approach has been to maximize overall cure rates, with the secondary purpose being to preserve the patient's bladder. The modalities used to ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
1
15
0
4
Order By: Relevance
“…It was reported that complete response (CR) to invasive bladder cancer was observed in 76-91% of cases, and the overall 5-year survival rate was 66-74% after induction of multimodality bladder preservation therapy using intraarterial chemotherapy [2,7,8]. These results are similar to those achieved by radical cystectomy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was reported that complete response (CR) to invasive bladder cancer was observed in 76-91% of cases, and the overall 5-year survival rate was 66-74% after induction of multimodality bladder preservation therapy using intraarterial chemotherapy [2,7,8]. These results are similar to those achieved by radical cystectomy.…”
Section: Discussionsupporting
confidence: 88%
“…However, there are some patients who do not choose radical cystectomy, although the neobladder would improve their quality of life (QOL). Several protocols for bladder preservation in cases of invasive bladder cancer have been reported [1][2][3]. Recently, multimodality bladder preservation therapy for invasive bladder cancer was found to have similar treatment efficacy to radical cystectomy.…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6][7] Briefly, several groups, including Harvard University in the USA, the University of Paris in France and the University of Erlangen in Germany, reported that the combination of TURBT, chemotherapy and radiotherapy yielded more favorable outcomes than those provided by monotherapies or other combinations of a subset of the three modalities. [8][9][10] Over the past two decades, trimodality therapy has been investigated in several prospective studies carried out mainly by the RTOG; 5-year OS rates ranged from 50% to 60%, which were comparable to those of RC series, 11,12 and 40-45% of the patients maintained their native bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque las pautas de preservació n vesical se desarrollaron inicialmente como una alternativa paliativa para pacientes que o bien no eran candidatos a recibir tratamiento quirú rgico mediante cistectomía radical o bien rechazaban este tratamiento, la experiencia acumulada ha ido puliendo las pautas y la selecció n de pacientes, y hoy, con alrededor de 1.000 casos documentados tratados con conservació n, podemos decir que en pacientes seleccionados se puede conservar la vejiga sin comprometer los niveles de supervivencia 7 . En todos los protocolos de conservació n, el tratamiento se divide en una fase de inducció n con quimioterapia-radioterapia con o sin quimioterapia neoadyuvante, una inmediata valoració n de la respuesta y un tratamiento de consolidació n con quimioterapia-radioterapia con o sin quimioterapia adyuvante.…”
Section: Discusió Nunclassified